Antitumor activity of synthetic naphthoquinone derivatives (review) - E. L. Golovina; V. A. Serebryakova; O. E. Vaizova (Разработка и регистрация лекарственных средств)
Introduction. Cancer is the leading cause of death worldwide. Naphthoquinones are a group of natural organic compounds with a wide range of activity, including cardio-, hepato-, neuroprotective effects, as well as antimicrobial, anti-inflammatory and antitumor activity. 1,4-naphthoquinone is easily oxidized, reduced, and may be easily attached with nucleophiles. Well-developed methods of chemical modification of naphthoquinones make them attractive for the development of new types substances. It is known about the antitumor effect of natural naphthoquinone compounds – plumbagin, shikonin, lapachol. Antitumor antibiotics such as doxorubicin and daunorubicin have a 1,4-naphthoquinone fragment in their structure.Text. This review is devoted to the analysis of information on the mechanisms of antitumor action of synthetic derivatives of 1,4-naphthoquinone. Possible targets of their antitumor action are discussed.Conclusion. An analysis of the literature data showed that synthetic compounds based on the 1,4-naphthoquinone molecule have antitumor activity. The mechanism of antitumor action may be associated with the induction of apoptosis through the signaling pathway of mitogen-activated protein kinase (MAPK) and the pathway of the signal transducer and activator of transcription 3 (STAT3), inhibition of cell division cycle phosphatase (Cdc25), accumulation of reactive oxygen species (ROS), inhibition of angiogenesis. The data obtained by researchers from different countries confirm the prospects of searching for new compounds with antitumor activity among synthetic derivatives of 1,4-naphthoquinone for the development of new medicines based on them.